Krinoi kai limenes : Studies in Honor of Joseph and Maria Shaw (Prehistory monographs, 2007)
Joseph and Maria Shaw received the Archaeological Institute of America's Gold Medal for a lifetime of outstanding achievement in January of 2006. This volume is a collection of the papers presented at the Gold Medal Colloquium held in their honour during the 2006 Annual Meeting of the Archaeological Institute of America in Montreal, Quebec. Additional articles have also been written for this volume. Many of the articles pertain to different aspects of Aegean Bronze Age architecture, harbors, frescoes, and trade, which are all keen interests of the Shaws